An interpretative perspective of the Mocoví’s living. The case of Com Caia Mocoví community from Campo San José.: El caso de la comunidad mocoví Com Caia de Campo San José (Desarrollo, Estado y Espacio, 2023)
This investigation analyzes from an architectural disciplinary perspective the situation of the landscape, the territory and the community facilities of the Com Caia Mocoví community, based on the consideration of its cultural and historical particularities and the reinterpretation of its ways of living.The case of study addresses the community located in Campo San Jose, which is situated in Recreo’s rural area.   This settlement is comprised of lands given by the provincial government to the Com Caia Mocovi community in the year 2008 to contribute to the historical reparation.  These lands are not part of the ancestral territories that were originally inhabited by the Mocoví people.  This situation, combined with the historical persecutions, the different processes of marginalisation and relocations to which they were subjected, are evident in the problems related to territorial and, therefore, landscape appropriation. Another manifestation of this problem can be seen in the facilities and communal spaces, understood as settings of cultural manifestation and as expressions of the ways of living.This situation causes cultural practices to see their reproduction limited, since the community must adapt its desires and needs to the existing possibilities, this complicating the cultural claim process and preventing the intangible heritage to be transferred to the tangible heritage.
Keywords: native people; mocoví; community facilities; landscape